Continuous fractionation of glycerol acetates. Physicochemical properties glycerol acetates + CO2 mixtures at high pressure - Pereda, Selva (2020)
Glycerol acetates are high-added value biosurfactants that find applications in different industrial sectors. Previous studies show the supercritical CO2 technology has a great potential for the fractionation of these highly viscous, amphiphilic, and non-volatile products (mono, di, and triacetyl glycerol) according to the quality standards of the food and cosmetic industry [1-3]. A proper design of fractionation columns and their further scale-up to commercial scale requires a robust thermodynamic model for phase equilibrium and PVT predictions [4], as well as proper correlations for physical properties like viscosity to assess the mass transfer and estimate the height of theoretical stages [5]. Physiochemical properties of these multicomponent mixtures are difficult to predict due to the complex nature of this system [6]. Thus, in this work, we determine experimentally the density and viscosity of CO2 saturated glycerol acetates mixtures at different pressures (30 bar to 150 bar), temperatures (25 °C to 50 °C) and CO2 concentrations (30 mol % to 70 mol %). Operating conditions were selected based on phase equilibrium predictions with the GCA-EOS of a high-pressure fractionation column [2]. First, a variable volume equilibrium cell is used to measure bubble points and saturated liquid molar volumes of glycerol acetates + CO2 mixtures. Thereafter, a high-pressure falling ball type viscometer is used to determine the dynamic viscosity of saturated liquid mixtures in the same range of pressure, temperature and CO2 concentrations.